2019
DOI: 10.1371/journal.ppat.1007662
|View full text |Cite
|
Sign up to set email alerts
|

Full restoration of specific infectivity and strain properties from pure mammalian prion protein

Abstract: The protein-only hypothesis predicts that infectious mammalian prions are composed solely of PrP Sc , a misfolded conformer of the normal prion protein, PrP C . However, protein-only PrP Sc preparations lack significant levels of prion infectivity, leading to the alternative hypothesis that cofactor molecules are required to form infectious prions. Here, we show that prions with parental strain properties and full specific infectivity can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 84 publications
1
41
0
Order By: Relevance
“…However, it has been shown that PrP Sc glycosylation is not absolutely required for strain-dependent prion neurotropism, as unglycosylated RML and 301C inoculum maintain their strain-specific PrP Sc distribution and vacuolation [48]. Additionally, we recently showed that a recombinant PrP Sc conformer lacking glycosylation displays same pattern of neurotropism as the same strain of native PrP Sc [34]. Finally, the "coprion" hypothesis [49] posits that small, replicating nucleic acids encode prion strain information, but no such molecules have ever been discovered.…”
Section: Plos Pathogensmentioning
confidence: 96%
See 4 more Smart Citations
“…However, it has been shown that PrP Sc glycosylation is not absolutely required for strain-dependent prion neurotropism, as unglycosylated RML and 301C inoculum maintain their strain-specific PrP Sc distribution and vacuolation [48]. Additionally, we recently showed that a recombinant PrP Sc conformer lacking glycosylation displays same pattern of neurotropism as the same strain of native PrP Sc [34]. Finally, the "coprion" hypothesis [49] posits that small, replicating nucleic acids encode prion strain information, but no such molecules have ever been discovered.…”
Section: Plos Pathogensmentioning
confidence: 96%
“…Finally, we also investigated the cofactor preferences for a pair of matched recPrP Sc conformers which are derived from the same original seed, but subsequently propagated either in the presence or absence of phospholipid cofactor, and therefore termed "cofactor" and "protein-only" PrP Sc , respectively [16,33,34]. The results show that both conformers are able to use either purified phospholipid or poly(A) RNA as cofactors in sPMCA reactions using immunopurified native bank vole PrP C substrate (Fig 5, columns three and four).…”
Section: Plos Pathogensmentioning
confidence: 99%
See 3 more Smart Citations